CORRELATE OF ACADEMIC PERFORMANCE OF STUDENTS IN MATHEMATICS USING TWO DIFFERENT TEST FORMATS - Borisade Tunde Fidelis (European Scientific Journal, ESJ, 2012)
This paper examines the performances of students in Mathematics using two test formats. 100 students of SS1 were selected randomly from 5 secondary schools in Ikere-Ekiti as subjects for the research. Each of the students was assigned with each of the two test formats – Matching and Completion test formats. Three hypotheses were generated and tested at 0.05 level of significant. Result of the findings revealed that, there was a significant relationship in the performance of students in the two test formats. Finding also showed that there was no significant difference between the performance of boys and girls in the matching test format but a significant difference in the completion test format. It was recommended based on the findings that, emphasis should henceforth be shifted from the common type of objective, that is, the option type, YES/NO or TRUE/FALSE, to either or both completion or matching test formats. This will reduce the rate of cheating and other shortcomings often witnessed in the former type of objective test format.